Analysis of Guru Penggerak Program: Teacher Satisfaction and Method Implementation Across Different Demographics - Gusti, Valeria Yekti Kwasaning; Kandaga, Thesa; Nurhayati, Suci; Risnawati, Erna (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study evaluates the impact of the